Use of Linked Administrative Children's Social Care Data for Research: A Scoping Review of Existing UK Studies. (15th March 2022) - Allnatt, G; Elliott, M; Scourfield, J; Lee, A; Griffiths, L J
Abstract: Increasing access to children's social care data presents enormous potential for research and policy evaluation, with opportunities increased where data can be anonymously linked to other sources of information, such as health and education data. The purpose of this scoping review was to provide an overview of all UK data linkage studies that have used routinely collected individual-level children's social care administrative data. Six research databases were searched and twenty-five studies were identified as meeting the inclusion criteria, with the majority ( n  = 18) based on English data. Complexities and the time-consuming nature of these studies are highlighted, as are issues with missing data and inconsistencies in recording information across local authorities, impacting on the linkage process. Increased access to such data, and improvements to data capture, could improve the utility of these valuable administrative data assets in the social care sector. Abstract : UK Governments hold a substantial amount of information which is routinely collected about individual children and families who receive care and support from social care services. Due to advances in digital technology, it is now possible to link individual records anonymously across different sectors such as health and education to provide a holistic picture of issues affecting this population. For this paper, we identified twenty-five studies that made use of data linkage techniques to answer complex research questions about children receiving welfare interventions. We provide a summary of these and outline benefits and challenges experienced in the data linkage process. We conclude that data linkage research in this field offers new evidence opportunities relevant for policy and practice in children's social care.